A bibliometric analysis of the 100 top-cited systematic review and meta-analysis in Orthodontics - Madhanraj SELVARAJ; Bhaskar NIVETHITHA; Piramanayagam VARSHITHA; Ulaganathan SANGEETHA; Balasubramanian MADHAN (Dental Press Editora, 2024)
ABSTRACT Objective: This bibliometric study aimed to analyze the citation metrics, journal and author characteristics, and subject domains of the 100 top-cited Systematic Reviews (SR) and Meta-Analysis (MA) in orthodontics. Material and Methods: An electronic database search was conducted for SR and MA in the Web of Science on 16th July 2023, without language and time restrictions. Of the 802 hits returned, the 100 top-cited orthodontic articles were shortlisted. They were analyzed for citation metrics, journal characteristics (journal, year of publication, impact factor-IF), author and affiliation characteristics (number, primary and corresponding author's affiliation, and country), study domain, and keywords. Results: These articles were published from 1996 to 2021 in 20 journals, with an impact factor of 1.9 to 10.5, by 351 researchers affiliated with 104 universities. Their citations ranged from 45 to 344, and 34 poised to be classified as classic (≥ 100 citations). The maximum number of articles was published in the American Journal of Orthodontics and Dentofacial Orthopedics (n=38), the European Journal of Orthodontics (n=18), and the Angle Orthodontist (n=8). The authors for individual papers ranged from 1 to 10, with 5 being the most common (n=58). Europe had the highest contribution regarding the number of corresponding authors, institutions, and citations. Bone anchorage and orthodontic tooth movement/Biomechanics were the most frequently researched domains (n=11 each). The most common keyword used was Orthodontics (n=19), followed by Systematic Review (n=16) and Meta-analysis (n=9). Conclusion: In general, the top cited SR and MA were published in high-impact orthodontic journals, were multi-authored, and reflected the collaborative work from different universities.